Does Aid for Trade affect the quality of the environment? Evidence from Aid for Trade recipient countries - Ly-My, Dung (2023)
The positive impacts of Aid for Trade (AfT) have been well examined on various aspects such as trade, trade liberty, inward foreign direct investment (FDI), infrastructure and so forth. However, the environmental effects of AfT have never been examined, while the environmental impact of foreign aid is already confirmed in the literature. To the best of our knowledge, this is the first paper that investigated the connection between AfT and the quality of the environment in recipient countries. Using data from 100 countries from 2003 to 2019 with system generalised method of moment (GMM) estimator, our research results confirmed that AfT has a negative impact on the environmental quality of recipient countries, and we offer further explanations about this. However, the negative effect of AfT on environmental quality can be varied depending on the institutional quality and level of economic development of recipient countries.